Mapping Mobility: Women and Textual Networks in the Fifteenth-Century Prose Epic 'Herzog Herpin' (Interfaces: A Journal of Medieval European Literatures, 2022)
Considering the example of the fifteenth-century prose epic Herzog Herpin, attributed to Elisabeth of Nassau-Saarbrücken, through the lens of Caroline Levine's approach to networks, this essay examines the constitutive role of women in intra- and extra-textual constellations. Herzog Herpin is structured by networks colliding and interacting with each other. The family whose story it follows, the Mediterranean space that condition the movement of family members, and the network of intertextual references to Arthurian and Carolingian materials offer particularly productive examples of forms in which women act as connective agents. In turn, Herzog Herpin's composition is conditioned by the context in which Elisabeth evolves – a dynastic network in which women foster links between courts. Using a network approach to connect the intra- and extra-textual without implying causality, sheds light on a pattern of gender-specific involvement in literature relying on movement and connectivity.
Keywords: network; intertextuality; women; mobility; culture